PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM - Bisara, Chrismas; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to examine the influence of financial performance which is proxy by current ratio, debt to equity ratio, return on asset, and total asset turnover to the stock return which is measured by using capital gain/loss plus dividend yield on the manufacturing companies which are listed in Indonesia Stock Exchange (IDX) in the years of 2011-2013. The sample collection method has been carried out by conducting purposive sampling and the samples are thirty two manufacturing companies. The dependent variable is the Stock Return whereas the independent variables are Current Ratio, Debt to Equity Ratio, Return on Asset, and Total Asset Turn Over. The multiple linear regressions analysis is used as the data analysis method. The result of goodness of fit test shows that Current Ratio, Debt to Equity Ratio, Return on Asset, and Total Asset Turnover are the explanatory variables of the stock return. The result of the hypothesis test shows that Return on Asset has positive and significant influence to the stock return whereas Current Ratio, Debt to Equity Ratio, Total Asset Turnover do not have any significant influence to the stock return.Keywords: Current Ratio, Debt to Equity Ratio, Return on Asset, Total Asset Turnover and Stock return